Shaiva figure at the Government Museum in Sikar - Temples of India Project Team (Jio Institute, 2024)
This elegant Shaiva figure, originally part of a devakostha or sculptural niche adorning the walls of a now-lost Shaiva shrine, is now housed in the Government Museum, Sikar. The figure is depicted with four hands, the upper two hold a skull-scepter and cobras, while the lower left-hand holds a cup, or rather a skull, with the fingers of the right hand dipping into its contents. On the left is an image of a vyala, which was once placed in the salilantara recess of the temple wall. Ichnographically, the figure reflects a tantric influence. The symbolism of the cup or skull likely represents the spiritual nectar of bliss attained through the completion of tantric sadhana, a concept shared in both Shaiva and Buddhist tantric traditions. Iconographically, the figure reflects a tantric influence. The symbolism of the cup or skull likely represents the spiritual nectar of bliss attained through the completion of tantric sadhana, a concept shared in both Shaiva and Buddhist tantric traditions.